(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: This study aimed to explore the relationship between soldiers’ health literacy, their participation in organised sports, and their engagement in leisure-time physical activity. Methods: This cross-sectional study included 603 professional soldiers (494 males and 109 females; mean age = 39.08, standard deviation (SD) = 8.89) with service experience ranging from one to 33 years. Participants represented various branches of the armed forces. General health literacy was assessed using the short-form version of the Health Literacy Survey (HLS19-Q12). Leisure-time physical activity was measured by asking how many times per week participants engaged in vigorous physical activity for at least 30 minutes that increased their breathing and heart rate. Participation in organised sports activities was also recorded. Results: The average health literacy score was 80.10 (SD = 19.17), with 45.0% and 29.6% of participants exhibiting excellent and sufficient levels of health literacy, respectively. A total of 37.3% of soldiers reported participating in organised sports activities, with male soldiers participating significantly more than females (p < .01). On average, soldiers engaged in vigorous physical activity 3.65 days per week (SD = 1.75), with 50.4% reporting activity levels of four to seven days per week. Regression analysis showed that higher health literacy was significantly and positively associated with leisure-time physical activity (β = 0.21, p < .001; R² = 0.05, F = 7.49, p < .001). Conversely, health literacy was negatively associated with participation in organised sports (β = –0.13, p < .001; R² = 0.04, F = 5.44, p < .001). Conclusion: Overall, the findings suggest that soldiers generally possess high levels of health literacy and that many are physically active. Notably, health literacy was positively associated with leisure-time physical activity but negatively associated with participation in organised sports, indicating that these forms of physical activity may be influenced by different motivational or contextual factors.